Surgery for Obstructive Sleep Apnea in Obese Children: Literature Review and Meta-analysis. (June 2019) - Scheffler, Patrick; Wolter, Nikolaus E.; Narang, Indra; Amin, Reshma; Holler, Theresa; Ishman, Stacey L.; Propst, Evan J.
Objectives: Surgical intervention for obstructive sleep apnea (OSA) in overweight and obese children may not be as effective as it is in normal-weight children. The purpose of this study was to systematically review the effects of various surgical interventions for OSA in obese children and to meta-analyze the current data. Data Sources: PubMed, OVID, and Cochrane databases. Review Methods: Databases were searched for studies examining adenotonsillectomy, uvulopalatopharyngoplasty, supraglottoplasty, or tongue base surgeries and combinations in obese children with OSA. Adenotonsillectomy was the only procedure with enough data for meta-analysis; polysomnographic data were extracted and analyzed using a random-effects model. Results: For adenotonsillectomy, 11 studies were included in the meta-analysis. Despite significant improvement in the apnea-hypopnea index (22.9 to 8.1 events/h, P < .001), respiratory disturbance index (24.8 to 10.4 events/h, P < .001), and oxygen saturation nadir (78.4% to 87.0%, P < .001), rates of persistent OSA ranged from 51% to 66%, depending on the outcome criterion used. There was evidence of limited effectiveness for surgical interventions to treat OSA in obese children using uvulopalatoplasty (12.5%) and tongue base surgery (74%-88%). Conclusions: Surgical interventions for OSA in overweight and obese children are effective at reducing OSA but with higher rates of persistent OSA than reported for normal-weight children. However, the amount of reduction appears to vary by surgical procedure. More attention should be paid toward preoperative weight loss and patient selection, and parents should be provided with realistic postoperative expectations in this difficult-to-treat population.